2021
DOI: 10.3389/fonc.2021.670085
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Histopathology of Pancreatic Ductal Adenocarcinoma by Intravoxel Incoherent Motion-Diffusion Weighted Imaging Comparing With Diffusion-Weighted Imaging

Abstract: ObjectivesTo explore the differences between intravoxel incoherent motion diffusion-weighted imaging (IVIM-DWI) and diffusion-weighted imaging (DWI) in evaluating the histopathological characters of pancreatic ductal adenocarcinoma (PDAC).MethodsThis retrospective study enrolled 50 patients with PDAC confirmed by pathology from December 2018 to May 2020. All patients underwent DWI and IVIM-DWI before surgeries. Patients were classified into low- and high-fibrosis groups. Apparent diffusion coefficient (ADC), d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…100,102 In contrast, a significant positive correlation was detected in perfusion fraction (f ). 100,102 The differentiation of autoimmune pancreatitis from PDAC is challenging. Four studies reported a significantly smaller ADC in autoimmune pancreatitis than in PDAC, 77,[103][104][105] whereas 3 other investigations did not show a significant difference.…”
Section: Proton Density Fat Fractionmentioning
confidence: 88%
See 2 more Smart Citations
“…100,102 In contrast, a significant positive correlation was detected in perfusion fraction (f ). 100,102 The differentiation of autoimmune pancreatitis from PDAC is challenging. Four studies reported a significantly smaller ADC in autoimmune pancreatitis than in PDAC, 77,[103][104][105] whereas 3 other investigations did not show a significant difference.…”
Section: Proton Density Fat Fractionmentioning
confidence: 88%
“…Two studies revealed a significant negative correlation of tumor fibrosis with pure diffusion (D) 100,102 . In contrast, a significant positive correlation was detected in perfusion fraction ( f ) 100,102 …”
Section: Relaxation Timesmentioning
confidence: 99%
See 1 more Smart Citation
“…This avoids the influence of cystic and vascular areas, which have a higher diffusion capacity of water molecules 33 on ADC values, which would misrepresent the true ADC values of tumor parenchymal areas. Meanwhile, Mannelli et al 34 and Liu et al 35 highlighted that small vision DWI can reduce artifacts and improve image resolution, resulting in an accurate ADC measurement. Therefore, sADC may be more representative of the ADC of the true pancreatic tumor microenvironment.…”
Section: Single‐parameter Functional Diffusion‐weighted‐mrimentioning
confidence: 99%
“…IVIM DW imaging compensates for the downsides of traditional DWI because it is able to separate water molecule diffusion and microcirculatory perfusion-related diffusion. Changes in IVIM-derived parameters are associated with significant changes in advanced pancreatic fibrosis, which often accompanies pancreatic steatosis [22,32].…”
Section: Magnetic Resonance Imaging and Pancreaticmentioning
confidence: 99%